SIRT1 and exercise-induced bone metabolism: a regulatory nexus - Liu, Lijie; Zhang, Jiale; Cui, Runhong; Wang, Na; Zhang, Yun; Liu, Lifei; Zhang, Xinan; Liu, Qingfeng (Frontiers in Cell and Developmental Biology, 2025)
Regular exercise positively influences bone health, enhances bone density and strength, and reduces the risk of osteoporosis. Silent information regulator of transcription 1 (SIRT1) is a deacetylase that plays a pivotal role in the regulation of various biological processes. In this review, we explore the role of SIRT1 in modulating bone metabolism in response to exercise. SIRT1 regulates crucial cellular processes, including inflammation, aging, autophagy, and oxidative stress, in bone cells such as bone marrow mesenchymal stem cells, osteoblasts, and osteoclasts, in response to exercise-induced stimuli. Notably, exercise influences bone metabolism by modulating muscle metabolism and neurotransmitters, with SIRT1 acting as a key mediator. A comprehensive understanding of SIRT1’s regulatory mechanisms will facilitate a deeper exploration of the principles underlying exercise-induced improvements in bone metabolism, ultimately providing novel insights into the treatment of bone metabolic disorders.